Attitudes Toward Homosexuality and Perceptions of the United States Abroad*. (30th November 2018) - Kim, Myunghee; Mirilovic, Nikola; Knuckey, Jonathan
Abstract : Objective: This article examines the determinants of perceptions of the United States and of President Obama among global citizens. Methods: The 2013 Pew Research Center's Global Attitudes surveys covering countries from Asia, Europe, the Middle East, the Americas, and Africa with diverse socioeconomic and religious backgrounds are analyzed by using multilevel estimates. Results: Findings reveal that attitudes toward homosexuality systematically shape opinions toward the United States and toward Obama's handling of foreign affairs. We also find the significant impact of religious and economic variables on perceptions of the United States and of Obama above and beyond other explanatory variables. Conclusion: This research demonstrates the relevance of cleavages regarding social values. It also contributes to larger debates about sources of anti‐Americanism, and, more generally, about the role of ideology and social values in international relations.